Social Networking Sites and Misinformation Challenges in Post-Truth Era: Moroccan Students in Tertiary Education as a Case Study - El Kandoussi, Mohamed (European Scientific Journal, ESJ, 2023)
The primary purpose of this study is to explore how Moroccan university students approach the various social networking sites and to assess their self-perceived capacities to critically analyze and evaluate digital content in general and online news and information more specifically. The paper poses several research questions that all aim to investigate the issue under examination. This empirical endeavor, that used the survey as a research instrument to gather data, closes by presenting a number of conclusions and recommendations for the Moroccan policy makers, stakeholders, and all concerned parties. The study especially reported how most respondents advance that they critically evaluate social media content and that they largely deploy various efficient verification measures and techniques. In the same vein, the sweeping majority of respondents highly rated their digital media perceived self-efficacy. Almost two thirds of the participants postulate that higher educational institutions should incorporate digital literacy skills in their curricula and syllabi.